The role of the microbiome and transcriptome in the development and progression of CIN - A. V. Peremykina (Медицинский совет, 2021)
The article presents a systematic review of the results of modern clinical studies devoted to the problem of the microbiome and transcriptome in women with cervical intraepithelial neoplasia (CIN). Moderate to severe CIN (CIN II – III) can precede the development of cervical cancer (CC) by several years or even decades. Cervical cancer (CC) is an important global health problem. There is a year-on-year increase in the prevalence of CC. Currently, there are many known risk factors that contribute to the development of CIN and cervical cancer. However, the vaginal and cervical microbiome play an important role in the development and progression of CIN and CC, according to some authors. Thus, the timely detection and treatment of cervical intraepithelial lesion-associated genital infections is now especially important. From these point of view, bacterial vaginosis (BV) is considered an acute problem in gynecological practice, which affects the incidence of precancerous conditions of the cervix. The results of the studies have shown the importance of detailed analysis of the vaginal microbial community, which was performed by the method of next generation sequencing (NGS). These studies were conducted using the NGS method based on the analysis of bacterial 16S rRNA genes, which has a high diagnostic accuracy and allows to determine the verity of the microbial landscape. The study of the transcriptome in women with CIN showed a change in many microRNA molecules, which can become markers of the CIN and cervical cancer upon further study. The introduction of the NGS method into the laboratory diagnostics complex will improve the diagnosis and timely prevent the progression of CIN to cervical cancer.The study of the microbiome of the vaginal biotope and cervical canal will allow to identify the groups of patients at high risk for the progression of precancerous lesions of the cervix and cervical cancer. Transcriptome studies have shown changes in many microRNA molecules (SALL4, FOXO1, HBD-1, HBD-2, HBD-3, LL37, psoriasin and IL-8, etc.) in women with CIN and cervical cancer.